On the ICT Economy in the European Countries: Investigating the Contribution of the ICT Sectors Using the Input-Output Model - Ibrahim Kholilul Rohman; Erik Bohlin (International Telecommunications Society (ITS), 2010)
Investigating the Contribution of the ICT Sectors Using the Input-Output Model Previous studies have been devoted to investigating the future of economic growth and examining the importance of technology and the ICT sectors in accelerating the growth of the economy. These studies are from a macro perspective that emphasizes the role of infrastructure investment, as well as from the firm level analysis, which is mainly related to cost efficiency. In addition, recent studies of the European countries indicate that the region is now facing a weakening effect regarding the contribution of the knowledge economy, which slows economic growth. This study aims at investigating the contribution of the ICT sectors in driving economic performance in the European economies with a sectoral approach using the Input-Output (IO) methodology. The method measures the contribution of ICT sectors based on the OECD's definition (2009) and decomposing it into several variables. In addition, the study focuses on investigating one decomposition factor related to technological change effects. The results indicate that the growth of ICT sectors' output declined considerably during 2000-2005 compared to 1995-2000. The decomposition analysis found that the ICT sectors have lost the advantage of export and technological change effects. It has also been ascertained that the smaller impact of technological change effects is due to the lack of connection between the ICT sectors and other sectors on the production side. At country level, this analysis consistently explains this phenomenon, especially in Germany and Spain but fails to detect it in France, where the technological change effect remains stable given the lack of connection between ICT sectors and the rest of the economy.
Keywords: O11; O14; O32; O33; N84; 330; structural change; economic growth; ICT sectors; input-output; multiplier